دور الاختيار والتعيين كأحد ممارسات الموارد البشرية في تحسين الأداء التنظيمي دراسة ميدانية في جامعة تشرين - تركمان, حنان; البهلول, ذو الفقار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aims to study the relationship between the role of selection and appointment as one of human resource practices on the one hand, and organizational performance at Tishreen University on the other hand. The researcher distributed a questionnaire to a sample of employees at Tishreen University reached (490) questionnaires, were retrieved (412), valid for analysis (380). To test the relationship, the researcher used Student T-test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a decrease in the level of selection and appointment, as well as a decrease in the level of efficiency and effectiveness at Tishreen University. The research concluded that there is significant relationship between selection and appointment as a human resource practices, and organizational performance, thus existence of the role of selection and appointment in improving organizational performance at Tishreen University. The research found a set of recommendations and proposals regarding the necessity of developing the procedures of selection and appointment, and continuing to set standards that ensure the required quality of employees. هدف البحث إلى دراسة العلاقة بين دور الاختيار والتعيين كأحد ممارسات الموارد البشرية من جهة، وبين الأداء التنظيمي في جامعة تشرين من جهة ثانية، حيث قام الباحث بتوزيع استبانة على عينة من العاملين في جامعة تشرين بلغت (490) استبانة تم استرداد (412) استبانة، كان صالحاً منها للتحليل(380). ولاختبار العلاقة قام الباحث باستخدام اختبار T ستيودنت لعينة واحدة، وكذلك معامل ارتباط بيرسون. توصل البحث من خلال الدراسة إلى أن هناك انخفاض في مستوى الاختيار والتعيين، وكذلك انخفاض في مستوى كل من الكفاءة والفاعلية في جامعة تشرين. كما توصل البحث إلى وجود علاقة معنوية بين الاختيار والتعيين كأحد ممارسات الموارد البشرية، والأداء التنظيمي، وبالتالي وجود دور للاختيار والتعيين في تحسين الأداء التنظيمي في جامعة تشرين. وخلص البحث إلى مجموعة من التوصيات والمقترحات المتعلقة بضرورة تطوير إجراءات الاختيار والتعيين، والاستمرار في وضع المعايير التي تضمن الحصول على النوعية المطلوبة من العاملين.